(untitled) (Faridpur Medical College Journal, 2020)
Primary mucinous cystic tumors occurring in the renal pelvis or the entire pelvicaliceal system are uncommon. Most are mucinous cystadenoma and less frequently mucinous cystadenocarcinomas. In fact, the publications on these neoplasms are limited to a few cases. Because mucinous cystadenomas of kidney are exceedingly rare, little is known about their natural history, pathogenesis and clinicopathologic features. Herein, we describe a case of mucinous cystadenoma arising from the renal pelvis, which resembled hydronephrosis. The patient presented with a history of intermittent dull pain on the left loin for 6 months. He had no history of removing urinary calculus or long- standing chronic infection in urinary system. The histopathology was unique since the inner surface of the cyst was covered by a mucinous epithelium connected to a urothelium, a transition from non- neoplastic urothelium to mucinous epithelium. This suggests that mucinous cystadenoma of renal pelvis, like its malignant counterpart, may arise in foci of metaplastic mucinous areas. Faridpur Med. Coll. J. Jul 2019;14(2): 104-106